Gabapentin for presumed neuropathic ocular pain - Raman Michael (American Journal of Ophthalmology Case Reports, 2020)
Purpose: To report a case of chronic neuropathic ocular pain in a patient without visual complaints. Observations: A 37-year-old male with a history of bilateral laser-assisted in situ keratomileusis (LASIK) presented with pain symptoms of 8 months duration in the left eye. The prior LASIK surgery was complicated by corneal ectasia in the left eye requiring penetrating keratoplasty and subsequent placement of a glaucoma drainage implant for uncontrolled, elevated intraocular pressure. The patient was evaluated with a complete clinical examination, including Goldmann applanation tonometry, dilated fundus examination, fluorescein angiography, optical coherence tomography, and magnetic resonance imaging. After 3 weeks of treatment with gabapentin 300 mg BID, the patient reported complete resolution of the ocular pain. Conclusions and Importance: The pathophysiology of neuropathic ocular pain remains poorly understood. Clinical evaluation often reveals minimal ophthalmic exam findings, leading to an underdiagnosis of the condition by ophthalmologists. Gabapentin may be an underutilized medication in the treatment of chronic ocular pain.